Sinteza in uporaba organskih biorazgradljivih aerogelov za kontrolirano sproščanje aktivnih substanc - Veronovski, Anja (visokošolska dela, 2013)
A number of polymers has been nowadays used in the production of carriers for drug delivery applications. These polymers have to be safe, non-toxic, they should possess high surface area, appropriate surface chemistry and porosity, chemical stability and low costs of processing. One of these promising candidates are natural polysaccharides such as alginic acid sodium salt, guar gum, xanthan gum, agar and chitosan. Alginates were used in the present research with the aim of organic biodegradable aerogels preparation. They have been proved to be safe, stable, non-toxic and renewable and have low costs because of their abundance in nature and ease of processing. They are similar to extracellular matrix having high chemical versatility, good biological performance and cell or enzyme-controlled degradability. Alginates are able to undergo reversible gelation in aqueous solution through interaction with divalent cations such as Sr2+, Ca2+ and Ba2+, which create ionic inter-chain bridges. The aim of the present research was to synthesize stable biodegradable aerogels used for controlled drug release of nicotinic acid and theophylline from the formulation. Two fundamental methods of ionic cross-linking were used to prepare alginate hydrogels: the diffusion method and the internal setting method. In the case of the first method cross-linkingis allowed by ion diffusion from a large outer reservoir into an alginate solution. Here single gel beads can be obtained. Also definite number of membranes was synthesized around spherical core to achieve even more controlled drug release. By internal setting method cationic ions are released in a controlled fashion from an inert cationic source within the alginate solution. Controlled release of ions is achieved by changing pH. Heremonolithic gel is obtained. After forming organic hydrogel by sol-gel method, the alcogels are formed by solvent exchange using 100% ethanol. Ethanol is later replaced by liquid CO2 with supercritical drying (100 bar, 40°C) and aerogel, used as a carrier of drugs, is obtained. Alginate aerogels were characterized by DSC, SEM and porosimetry. Drugs were added into alginate solution during sol-gel synthesis. The effects of the alginate concentration, viscosity and synthesis methods on model drug nicotinic acid and theophylline release were investigated. The results showed that by increasing alginate concentration and viscosity of alginate solution more cross-linked aerogels with higher mechanical strength were obtained. Moreover,after using the internal setting method synthesized carriers were more successful to retain drug inside the formulation, what resulted in inhibited drug release. The influence of dug release from multi-membrane spherical aerogels was also studied dependent on alginate solution concentration and CaCl2 and BaCl2 concentration. Since alginate is ionic polysaccharide, the resultant alginate aerogel is expected to bind ionic drugs and release them slower. The effect of the number of membranes on model drugs nicotinic acid and theophylline loading and release was also investigated. Results show that by adding more membranes around the core and using Ca2+ for ionic cross-linking nicotinic acid release was prolonged. Retarded theophylline release was obtained only by using Ba2+ ions for alginate cross-linking. By increasing membrane number and BaCl2 concentration theophylline release was successfully extended, namely in all cases drug release became linear versus time. In the case of nicotinic acid loading increased by adding more membranes around the core, however for theophylline the opposite results were obtained, namely due to the nature of model drugs.
Keywords: Aerogeli; aerogels; controlled drug release; Disertacije; drug carriers; kontrolirano dostavljanje aktivnih substanc; naravni polisaharidi; natural polysaccharides; nosilci aktivnih substanc; organic biodegradable aerogels; organski biorazgradljivi geli; Polisaharidi; sol-gel sinteza; sol-gel synthesis